PENDAPATAN DAN RISIKO PENDAPATAN USAHA TANI PADI DAERAH IRIGASI DAN NON IRIGASI DI KABUPATEN BANJAR KALIMANTAN SELATAN - Ani Suryantini, Muzdalifah, Masyhuri (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2012)
This study aims to determine the income and revenue risk from rice farming inirrigated and non irrigated land are also factors that influence it. The hypothesisadvanced is that (1) factors that affect revenue and revenue risk rice farming inpaddy fields are irrigated and non irrigated land area, the price of seed, fertilizerprices, wage labor, the price of seeds, irrigation areas and varieties, (2 ) rice farmincome risk in irrigated land is lower than non-irrigated land. Data obtainedthrough interviews with 80 randomly simple rice farmers. The method used ismultiple linear regression analysis model with Ordinary Least Square (OLS) andthe analytical coefficient of variation (CV). The results showed that the area ofland, the price of urea, ponska price, the price of pesticides, and irrigation areadummy effect on income. While the risk is influenced by the land revenue, theprice of seed, the price of urea fertilizer, fertilizer prices ponska, pesticide pricingand superior varieties of variables. Income risk in the area of irrigated ricefarming was smaller than non-irrigated areas with kofisien variation of 0.83 and0.89.Key words: revenue, risk, rice, irrigated and non irrigated area.